Mengembangkan Minat Belajar Huruf Hijaiyah Pada Anak Menggunakan Media Interaktif Berbasis 2D - Yunika, Astri; Imanullah, Muhammad; Darnita, Yulia; Marhalim, Marhalim (Institut Bakti Nusantara, 2024)
This research discusses the importance of learning Hijaiyah letters for Muslims, as these are the basic letters for reading the Quran. To enhance children's ability to recognize Hijaiyah letters, the author attempts to use learning strategies through interactive media for children. The problems addressed in this study are how to develop children's interest in learning Hijaiyah letters using 2D-based interactive media and how the interest in learning Hijaiyah letters is influenced by using 2D-based interactive media. This study aims to determine the extent to which the development of interest in learning Hijaiyah letters in children is achieved using 2D-based interactive media. The results of this study show that the average results of children in learning Hijaiyah letters with the help of interactive media received very good responses in each choice. Thirty-six respondents answered